2018
DOI: 10.1097/ajp.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Pain-related Activity Management Patterns and Function in Patients With Fibromyalgia Syndrome

Abstract: The findings confirm the importance of pain-related activity management patterns as predictors of patient function, and support the necessity of addressing these factors in chronic pain treatment. In addition, the results suggest that targeting increases in activity pacing and decreases in pain avoidance, specifically, might yield the best patient outcomes. However, further research to evaluate this possibility is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 37 publications
3
46
3
1
Order By: Relevance
“…If we compare the effect with gender, it also partially compensates for the influence of female gender on physical performances during FCE. e influence of the overdoing/persistence pattern is debated in the literature, which is mainly based on subjective measures: Cane et al found a positive association with disability in a population of patients with chronic pain recruited from a pain clinic, with a median pain duration of 7 years, and a high proportion of fibromyalgia, in contrast to our population [5], whereas others found mixed associations of task persistence [6,8], or no association [47]. e association of overdoing/persistence with better functioning seems to be in accordance to those of Hasenbring, who found a lower perceived disability in a subgroup of patients called "eustress-endurant" [48], and with Luthi who found positive associations of overdoing/persistence with functioning [22].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…If we compare the effect with gender, it also partially compensates for the influence of female gender on physical performances during FCE. e influence of the overdoing/persistence pattern is debated in the literature, which is mainly based on subjective measures: Cane et al found a positive association with disability in a population of patients with chronic pain recruited from a pain clinic, with a median pain duration of 7 years, and a high proportion of fibromyalgia, in contrast to our population [5], whereas others found mixed associations of task persistence [6,8], or no association [47]. e association of overdoing/persistence with better functioning seems to be in accordance to those of Hasenbring, who found a lower perceived disability in a subgroup of patients called "eustress-endurant" [48], and with Luthi who found positive associations of overdoing/persistence with functioning [22].…”
Section: Discussionmentioning
confidence: 93%
“…We found no association between the avoidance pattern and any of the 4 FCE tests. ese results may seem surprising at first glance, as this pattern is associated with poor functioning in the literature [7,15,47,55]. However, the few studies that also used observational measures of physical activity showed that there was more often no significant influence [10,12,22].…”
Section: Discussionmentioning
confidence: 96%
“…Physical inactivity and sedentary lifestyles, and the associated increase in body mass index (BMI), have been suggested as factors associated with FMS 33,34. Activity avoidance is associated with poorer function in individuals with chronic pain, and predicted poorer physical and psychological functioning and higher pain-related interference with daily life 35. Overactive patterns can also contribute in the long term to increased risk of pain exacerbation, and patients with an overactive coping style when engaging in daily life activities usually report poorer physical and psychological function 35.…”
Section: Vulnerability Factors In Fibromyalgiamentioning
confidence: 99%
“…Activity avoidance is associated with poorer function in individuals with chronic pain, and predicted poorer physical and psychological functioning and higher pain-related interference with daily life 35. Overactive patterns can also contribute in the long term to increased risk of pain exacerbation, and patients with an overactive coping style when engaging in daily life activities usually report poorer physical and psychological function 35. In contrast, patients who pace themselves (such as by slowing down and taking breaks to facilitate goal attainment) in their daily activities report lower pain interference and greater psychological function and pain control 35…”
Section: Vulnerability Factors In Fibromyalgiamentioning
confidence: 99%
“…First, studies have shown that certain activities, such as limiting the time standing, laying down in bed when in pain or going slow and steady despite the pain, correlate with both adaptive and maladaptive coping (Tan et al, 2011). Additionally, the nature of certain activity patterns appears to be inconsistent with the literature findings, showing that persistence and pacing have been unreliably associated with outcomes depending on how they are conceptualized (Hadzic et al, 2019;Kindermans et al, 2011;McCracken & Samuel, 2007;Racine et al, 2018). For example, persistence can be viewed as overdoing, which is often linked to an increase of pain, and is considered to be a maladaptive coping strategy (Luthi et al, 2018).…”
mentioning
confidence: 99%